2013
DOI: 10.1521/soco.2013.31.6.806
|View full text |Cite
|
Sign up to set email alerts
|

Do We Look Like Me or Like Us? Visual Projection as Self- or Ingroup-Projection

Abstract: People see their own group as more typical of a larger, superordinate category than they see other, included subgroups (ingroup-projection). This basic effect is not restricted to verbally encoded characteristics but also expands to the domain of what people think superordinate group members typically look like. Despite the robustness of the ingroup-projection phenomenon, it could be argued that it is a side effect of an even more basic process of seeing groups and individuals as similar primarily to the self … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 17 publications
0
19
1
Order By: Relevance
“…Ratings from a separate group of participants showed that each national group’s European CI appeared to resemble their own nationality—that is, the Germans’ CI of a European appeared more stereotypically German and less stereotypically Portuguese than the Portuguese participants’ CI of a European did. These findings demonstrate ingroup projection, whereby people project aspects of their own group onto other groups (here, their superordinate group; see also Imhoff & Dotsch, 2013). Assuming that Anglo- and Franco-Canadians mentally represent themselves differently, this raises the question of whether they might also mentally represent Canadians, as a whole, as more similar to their linguistic ingroup versus outgroup.…”
Section: Mentally Representing Nationalitymentioning
confidence: 72%
“…Ratings from a separate group of participants showed that each national group’s European CI appeared to resemble their own nationality—that is, the Germans’ CI of a European appeared more stereotypically German and less stereotypically Portuguese than the Portuguese participants’ CI of a European did. These findings demonstrate ingroup projection, whereby people project aspects of their own group onto other groups (here, their superordinate group; see also Imhoff & Dotsch, 2013). Assuming that Anglo- and Franco-Canadians mentally represent themselves differently, this raises the question of whether they might also mentally represent Canadians, as a whole, as more similar to their linguistic ingroup versus outgroup.…”
Section: Mentally Representing Nationalitymentioning
confidence: 72%
“…Previous research using the reverse-correlation task suggests that 20 to 30 participants per experimental cell tend to be sufficient to observe large effects (Dotsch & Todorov, 2012; Imhoff & Dotsch, 2013). Hence, we aimed to recruit at least 60 participants for this three-condition, between-group design.…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, ingroup norms were more strongly associated with participants' judgments than outgroup norms. This result may have emerged because individuals typically perceive ingroup members as more similar to themselves than outgroup members (Imhoff & Dotsch, 2013) and may therefore find ingroup norms to be more informative for how they should behave and what they should believe. Thus, Studies 3-4 also provided some support for the perceived outgroup irrelevance hypothesis.…”
Section: Theoretical Implicationsmentioning
confidence: 99%